The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1128/msphere.00663-22
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Screen in Macrophages Defines Host Genes Regulating the Uptake of Mycobacterium abscessus

Abstract: Pathogen interactions with immune cells like macrophages contribute to pathogenesis, yet the mechanisms underlying these interactions remain largely undefined. For emerging respiratory pathogens, like Mycobacterium abscessus , understanding these host-pathogen interactions is important to fully understand disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Additionally, Mycobacterium abscessus was found to cause increasing community- and hospital-acquired infections in humans ( 197 ). In 2023, a study transduced murine macrophages with a genome-wide knockout library to generally define and characterize important regulators in macrophage- M. abscessus interactions, such as sulfated glycosaminoglycans(sGAG) ( 198 ). They found that macrophage- M. abscessus interactions were mainly regulated by sGAG.…”
Section: Crispr Screening In Immune Cellsmentioning
confidence: 99%
“…Additionally, Mycobacterium abscessus was found to cause increasing community- and hospital-acquired infections in humans ( 197 ). In 2023, a study transduced murine macrophages with a genome-wide knockout library to generally define and characterize important regulators in macrophage- M. abscessus interactions, such as sulfated glycosaminoglycans(sGAG) ( 198 ). They found that macrophage- M. abscessus interactions were mainly regulated by sGAG.…”
Section: Crispr Screening In Immune Cellsmentioning
confidence: 99%